Semiotic Analysis of Bca Advertisement: “Don't Know? Kasih No! “As A Communication of Phishing Prevention Efforts - Teguh Iman Prasetya (International Journal of Education, Vocational and Social Science, 2025)
Semiotics is the study of signs and signaling systems that enable communication, especially in conveying meaning across various cultural contexts. In BCA's advertisement “Don't Know? Kasih No!”, semiotics is used to convey phishing prevention messages through signs that the audience understands, thus educating the public regarding digital security. This research uses a qualitative approach with the Peirce semiotic analysis method to examine the meaning in BCA's advertisement “Don't Know? Kasih No!” on Youtube as a Social Media Platform. Data collection techniques through documentation studies and data analysis using Charles Sanders Peirce's semiotic analysis method, which identifies meaning through a triadic model that includes representamen/sign, object, and interpretant. The results showed that BCA's “Don't Know? Love No!” successfully educates the public about online fraud awareness through humor and Indro Warkop, which enhances the emotional connection with the audience. The positive response from the audience shows that the combination of entertainment and an important message about personal data protection is very effective, making it one of the best educational ads of 2023. Semiotic analysis revealed the use of icons, indices and symbols that reinforce the fraud prevention message, demonstrating BCA's commitment to its customers' data security.